2021
DOI: 10.1089/ast.2019.2211
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Maturation of Iron- and Sulfur-Rich Mars Analogues: Implications for the Diagenetic Stability of Biopolymers and Their Detection with Pyrolysis–Gas Chromatography–Mass Spectrometry

Abstract: Acidic iron-and sulfur-rich streams are appropriate analogues for the late Noachian and early Hesperian periods of martian history, when Mars exhibited extensive habitable environments. Any past life on Mars may have left behind diagnostic evidence of life that could be detected at the present day. For effective preservation, these remains must have avoided the harsh radiation flux at the martian surface, survived geological storage for billions of years, and remained detectable within their geochemical enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…The moieties most effected by the presence of the iron oxide(oxy)hydroxide substrate are the fatty acids, as these go from being from some of the most relatively abundant pyrolysis products to complete or almost complete loss as A. platensis content is decreased. Previous work by this group (Royle et al, 2021;Tan et al, 2021) has demonstrated that the presence of the same iron oxide/(oxy)hydroxide mineral substrates used here greatly promoted the cyclization, aromatization and oxidative polymerization of fatty acids. This suggests that the main alteration products detected from A. platensis pyrolysed on the iron oxide/(oxy)hydroxide substrates originate from fatty acid parent molecules.…”
Section: Effect Of Various Mineral Substrates On Detectability and Tr...mentioning
confidence: 82%
See 3 more Smart Citations
“…The moieties most effected by the presence of the iron oxide(oxy)hydroxide substrate are the fatty acids, as these go from being from some of the most relatively abundant pyrolysis products to complete or almost complete loss as A. platensis content is decreased. Previous work by this group (Royle et al, 2021;Tan et al, 2021) has demonstrated that the presence of the same iron oxide/(oxy)hydroxide mineral substrates used here greatly promoted the cyclization, aromatization and oxidative polymerization of fatty acids. This suggests that the main alteration products detected from A. platensis pyrolysed on the iron oxide/(oxy)hydroxide substrates originate from fatty acid parent molecules.…”
Section: Effect Of Various Mineral Substrates On Detectability and Tr...mentioning
confidence: 82%
“…With the lack of recent plate tectonics (Sleep, 1994), and a lower thermal gradient on Mars (Borlina et al, 2015), preservation in buried (and thereby shielded) sediments could be greatly enhanced (Royle et al, 2018b;Tan et al, 2021), therefore the detectability of biomarkers in the presence of Mars-relevant minerals is of particular interest. 25 However, the current study has ascertained that a larger microbial population/biomass is necessary in iron oxide/(oxy)hydroxide-rich sediments to be able to ascertain a biological source due to the iron-promoted alteration/transformation of biomolecules.…”
Section: Communities Of Photosynthetic Extremophiles (Including Cyano...mentioning
confidence: 99%
See 2 more Smart Citations
“…A few experimental studies have dealt with the preservation/degradation of organic-clay mixtures under simulated hydrothermal Martian conditions. Yet, these hydrous pyrolysis experiments have been conducted either using single molecules, such as RNA (Viennet et al, 2019) or glycine (Dalai et al, 2017;Gil-Lozano et al, 2020), or using complex natural samples (Tan et al, 2021), rather than using model microorganisms experimentally mixed within a pure synthetic mineral matrix, as previously done by some authors to document the effect of diagenesis under terrestrial conditions (Oehler and Schopf, 1971;Li et al, 2014;Picard et al, 2015;Alleon et al, 2016;Miot et al, 2017;Igisu et al, 2018). Here, we report results of laboratory experiments conducted using cells of a model microorganism (i.e., Escherichia coli cells) and pure saponite (a Mg-rich trioctahedral smectite) synthesized in the lab.…”
mentioning
confidence: 99%